EFEK REBUSAN RIMPANG SEGAR, REBUSAN RIMPANG KERING, MINYAK ATSIRI DAN KURKUMIN Curcuma xanthorriza Roxb. TERHADAP KADAR BILIRUBIN PADA TIKUS WISTAR JANTAN YANG DIINDUKSI PARASETAMOL - Fitriana Hayyu Arifah; Suwijiyo Pramono; Agung Endro Nugroho (Balai Besar Penelitian dan Pengembangan Tanaman Obat dan Obat Tradisional, 2018)
Javanese turmeric (Curcuma xanthorrhiza Roxb.) is a medicinal plant that can be developed for the treatment of liver disease. The aim of this study is to evaluate the decoction of fresh rhizome, decoction of dried rhizome, essential oils, and curcumin of Curcuma xanthorrhiza Roxb. against bilirubin level on paracetamol-induced male Wistar rats. Male Wistar rats were divided into 10 groups including group I and II were normal control and negative control, groups III, IV, and V received pretreatment of decoction of fresh rhizome 0,75 g/kgBW, 2,25 g/kgBW, and 6,75 g/kgBW, respectively for 9 days, Groups VI, VII, and VIII received pretreatment of decoction of dried rhizome 0,45 g/kgBW, 1,35 g/kgBW, and 4,05 g/kgBW, respectively for 9 days, group IX received pretreatment of essential oils 1,01 μl/kgBW for 9 days, group X received pretreatment of curcumin 75 μg/kgBW for 9 days. Groups II, III, IV, V, VI, VII, VIII, IX, and X on days 7, 8, and 9 induced paracetamol 3 g/kgBW. The blood was drained on day 0 and 4 after induction of paracetamol for bilirubin parameter study. Data were analyzed statistically using One-Way ANOVA test followed by LSD test with a 95% confidence level. The results showed that pretreatment of decoction of fresh rhizome 0,75 g/kgBW decrease the bilirubin level significantly (p<0,05) against the negative control. It can be concluded that pretreatment of decoction of fresh rhizome 0,75 g/kgBW was the best effect of decrease the bilirubin level.